Effects of e-animated instruction on primary school pupils’ academic performance in comprehension reading in Ondo State, Nigeria - Tunde-Awe, Bolajoko Margaret (Penerbit Universiti Kebangsaan Malaysia, 2022)
With the advancement in the field of Information Communication Technology (ICT), traditional method of teaching and learning may no longer suffice. The current generations of learners are “digital natives” and any Teachers that want to be relevant in this era must key into the current thinking of using technology to pass across knowledge. With this in mind, this paper examined the effects of E-animated instruction on primary school pupils’ comprehension reading in Ondo State. The study adopted a quasi–experimental research design involving pre-test and post-test groups. The populations for the study consist of all the primary school pupils in Akoko South West Local Government Area, Ondo State, Nigeria. Two public and two private primary schools were purposively selected for the study while the sample size was one hundred (100) primary Five (5) pupils comprising forty-seven male and fifty-three female who were randomly selected into experimental and control groups. The experimental group was taught using e-animated comprehension instruction while the control group was taught with the conventional method. The research instrument used for data collection was a comprehension passage extracted from the pupils’ textbook and re-invented in e-animation mode through the help of a programmer. Two research questions were raised while two research hypotheses were tested. The research questions were answered using mean and SD while t-test statistic was used to test the hypotheses at 0.05 level of significance. The findings show that e-animated instruction enhanced the academic performance of primary school pupils’ comprehension reading. On the basis of these findings, it was recommended among others that teachers take advantage of the various tools provided by ICT in instruction delivery as this will set the pace for other electronic learning among pupils.